The discovery of devil's gardens: an ant–plant mutualism in the cloud forests of the Eastern Amazon. (10th May 2016) - Salas-Lopez, Alex; Talaga, Stanislas; Lalagüe, Hadrien
Abstract: Devil's gardens are one of the most remarkable mutualistic associations between ants and plants. Myrmelachista ants eliminate all vegetation from around their host plants, resulting in wide forest clearings which have intrigued scientists from the start. Despite their noticeability, here we report the discovery of devil's gardens in remote highland cloud forests of the Eastern Amazon, more than 2000 km away from their nearest known analogues in Western Amazonia. We describe the ecological characteristics of these gardens and consider what factors could have produced the geographic isolation of Eastern Amazonian devil's gardens. Three hypotheses are investigated: (1) the host plant distribution restricts the distribution of the mutualism, (2) the ecological tolerances of Myrmelachista explain the isolation, and (3) the devil's gardens of the Eastern Amazon constitute relicts from ancient forest refugia. The distribution of the possible associated myrmecophytes and previously described ecological ranges of devil's gardens cannot explain their ecological restriction to cloud forests in Eastern Amazonia, but our discovery is consistent with the biogeographic refuge hypothesis (i.e. highlands along the Amazon Basin constitute refugia for humid forests that spread during the Cenozoic). Our finding opens exciting perspectives for comparative studies of the origin, ecology and evolutionary history of this ant–plant mutualism.